THE IMPACT OF VITAMIN D3 LEVELS ON INFERTILITY.: JPUMHS;2025:15:01,13-18. http://doi.org/10.46536/jpumhs/2025/15.01.590 - Palwasha1, Hajira Naila Rahu2, Altaf Khan Pathan3, Iftikhar Ali4, Nida noor5, Sidra6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Infertility is the fifth most serious global physical or mental health condition. It may have detrimental effects on both partners’ social, psychological, physical, and financial well-being. The literature reveals positive relationship between infertility and vitamin D3 level but data on their complex interaction is relatively scarce in Pakistan, highlighting the need for further research. OBJECTIVE: To examine the impact of vitamin D3 levels on infertility. METHODOLOGY: A cross-sectional investigation was conducted on 132 infertile and 132 fertile women selected through convenience sampling at the Gynecology and Obstetrics ward of the PMC hospital, Nawabshah, Pakistan. Data were collected through a questionnaire and entered and analyzed in computer software Statistical Package for Social Sciences (SPSS) version 25.0. The link between infertility and qualitative variables was examined using the chi-square test, and the mean difference in vitamin D3 across research groups was evaluated using the independent sample t test. A confidence interval of 95% was used for the study. RESULTS: Vitamin D3 deficiency and insufficiency were significantly higher in infertile women (53%, 18.9%) compared to fertile women (22%, 11.3%). Infertility significantly increases with the age of participants increased ranging from 3.8% in 20-25 years to 34.8% in 36-40 years. Infertility was higher in the middle class (81.1%) compared to the poor class (18.9%) and significantly higher in illiterates 43.2% followed by primary (30.3%) and low in graduation (3.8%). CONCLUSION: Infertile women had significantly greater levels of vitamin D3 inadequacy and insufficiency than fertile women. Besides Vitamin D3, Infertility was found to be associated with age and education of women. Initiatives such as vitamin D3 supplementation, improving women’s education and social status and health interventions should be implemented to address this issue.